Spinal Cord Infarction after Cervical Transforaminal Epidural Steroid Injection: Case Report and Literature Review - Moon, Jangsup (Case Rep Neurol, 2017)
INTRODUCTION: Transforaminal epidural steroid injection (TFESI) is a widely used nonsurgical procedure in the treatment of patients with radiculopathy. It is efficacious in relieving pain, but a number of complications are being reported. Recently, increasing frequency of major complications, such as spinal cord infarction and cerebral infarction, has been reported with the use of a particulate steroid within fluoroscopic-guided procedures. METHODS: We report a 49-year-old man with a history of chronic cervical radiculopathy, who experienced a devastating complication after TFESI. RESULTS: After 2 min of regular TFESI, the patient abruptly experienced muscle weakness in both upper extremities and within 5 min the patient became quadriplegic. Despite active rehabilitation, the patient remained bed-ridden 4 years after the catastrophic event. To our knowledge, this is the first reported case of spinal cord infarction that occurred after TFESI in Korea. CONCLUSION: Considering the risk of dreadful complications, which appear in an unpredictable manner, TFESI with fluoroscopic guidance should be done only with a nonparticulate steroid.